THE USE OF INSTAGRAM ACCOUNT IN CONSTRUCTING THE CONCEPT OF BEAUTY: A CASE ON “UNPAD GEULIS” - Nadiffa Habiba Makarim; Dindin Dimyati; Ardhariksa Zukhruf Kurniullah (ASPIRATION Journal, 2020)
New media is an Internet based media using sophisticated computers and mobile phones. One of them is Instagram having more than 800 million users from across the world. In Instagram there are quite a lot of new phenomena appearing and one of the phenomena in Indonesia is an account for beautiful students such as ‘UNPAD GEULIS’ in which such an account has more than 87,000 followers. This research aims to understand how ‘UNPAD GEULIS’ constructs concept of beauty through its Instagram account. The researchers also wanted to find out what kind of beauty standard used for selecting pictures to be uploaded on the account. This is a qualitative research which used a structured interview with the account owner of ‘UNPAD GEULIS’ to get the data needed. The result has shown that ‘UNPAD GEULIS’ indirectly constructs the concept of beauty by uploading pictures through 5 steps such as the recommendation, good Instagram feeds, beauty standard, achievements, and request of permission.